Investigation of mechanical and tribological properties of NiCrAlY/ZrO2-Y2O3 coatings obtained by detonation spraying - Д.Б. Буйткенов; Ж.Б. Сагдолдинa; Л.Г. Сулюбаева; А.Б. Набиолдина; Н.С. Райсов (Қарағанды университетінің хабаршысы. Физика сериясы)
In this study, multilayer gradient NiCrAlY/ZrO2-Y2O3 coatings obtained by detonation spraying in 1D (spot sputtering) and 2D (full-surface scanning sputtering) modes were investigated. The structure of coatings was analyzed using scanning electron microscopy and electron dispersion analysis, mechanical properties (hardness, modulus of elasticity) were determined using various techniques. The tribological characteristics of the coatings including abrasion resistance and coefficient of friction were also studied. It was determined that the coatings consist of alternating layers of NiCrAlY and ZrO2-Y2O3, creating a multilayer gradient structure. It was found that the NiCrAlY layers act as a bonding element, providing interlayer adhesion, and the ceramic ZrO2-Y2O3 layer serves as a thermal barrier protecting the substrate from high temperature loads. It was found that the coatings in 2D mode have high microhardness compared to coatings in 1D mode. It was determined that the hardness of coatings smoothly increases from the substrate to the surface layers due to the gradient increase in the content of ceramic materials. It was found that coatings obtained in 2D mode have better wear resistance and lower coefficient of friction compared to coatings in 1D mode, indicating the greater efficiency of coatings in dry friction conditions and their ability to prevent wear of the substrate material.